KONSEP PENDIDIKAN ISLAM DALAM HIZBUT TAHRIR - Haniah Mase (JURNAL INDO-ISLAMIKA, 2019)
Hizbuttahrir is synonymous with the Islamic caliphate or the establishment of an Islamic state. Since the beginning of this organization, it has actually proclaimed itself as an organization that was founded because of the failure of a number of previous organizations that wanted to establish an Islamic state such as the Muslim Brotherhood (IM). This paper will explain the other side of Hizbuttahrir related to the concept of education developed by Taqyuddin an-Nahbany, as the founder of Hizbuttahrir.